Answer:
x = 2/5
Explanation:
Solve for x:
x/3 + 2/3 = 2 x
Hint: | Combine x/3 + 2/3 into a single fraction.
x/3 + 2/3 = (x + 2)/3:
(x + 2)/3 = 2 x
Hint: | Make (x + 2)/3 = 2 x simpler by multiplying both sides by a constant.
Multiply both sides by 3:
(3 (x + 2))/3 = 3×2 x
Hint: | Cancel common terms in the numerator and denominator of (3 (x + 2))/3.
(3 (x + 2))/3 = 3/3×(x + 2) = x + 2:
x + 2 = 3×2 x
Hint: | Multiply 3 and 2 together.
3×2 = 6:
x + 2 = 6 x
Hint: | Move terms with x to the left hand side.
Subtract 6 x from both sides:
(x - 6 x) + 2 = 6 x - 6 x
Hint: | Combine like terms in x - 6 x.
x - 6 x = -5 x:
-5 x + 2 = 6 x - 6 x
Hint: | Look for the difference of two identical terms.
6 x - 6 x = 0:
2 - 5 x = 0
Hint: | Isolate terms with x to the left hand side.
Subtract 2 from both sides:
(2 - 2) - 5 x = -2
Hint: | Look for the difference of two identical terms.
2 - 2 = 0:
-5 x = -2
Hint: | Divide both sides by a constant to simplify the equation.
Divide both sides of -5 x = -2 by -5:
(-5 x)/(-5) = (-2)/(-5)
Hint: | Any nonzero number divided by itself is one.
(-5)/(-5) = 1:
x = (-2)/(-5)
Hint: | Simplify the sign of (-2)/(-5).
Multiply numerator and denominator of (-2)/(-5) by -1:
Answer: x = 2/5